STUDY OF THE FEATURES OF KEY HOLE DEFECT FORMATION DEPENDING ON THE TECHNOLOGICAL PARAMETERS OF MANUFACTURING USING LPBF TECHNOLOGY (Modern Problems of Metallurgy, 2025)
In the LPBF process, the part is formed by local melting of the powder by a laser, which creates a melt pool. Its stability determines the surface quality. One of the critical defects in the LPBF process is porosity, as it worsens the fatigue strength and reliability of structures. The work investigated the effect of laser melting parameters of the 316L powder material on the morphology of the molten pool and the formation of porosity, in particular, defects of the “Key Hole” type. The material for the research was experimental samples made of austenitic stainless steel 316L with a chemical composition in wt%: Cr=17.79; Ni=12.63; Mo=2.35; Mn=0.78; Si=0.64; С=0.016, with a particle size: 45±15 μm. Experimental studies were performed on a single-mode fiber ytterbium laser with a Flet-top energy profile, which is characterized by a uniform energy distribution across the laser beam cross-section. The process parameters included variable laser power (80–270 W), scanning speed (200–1050 mm/s), and laser beam diameter (75–175 μm). 808 tracks were analyzed, of which 46 cases recorded porosity of this type. It was established that it does not occur at scanning speeds above 600 mm/s, and an increase in energy density contributes to its formation. It was established that the decrease in the number of defects with increasing laser power is associated with improved melt fluidity and its ability to more effectively absorb radiation energy. Under such conditions, gas inclusions have time to reach the surface by the time the “Key Hole” closes, which reduces the likelihood of porosity formation. Experimental studies have shown that the threshold value is close to 0.8, but it is not fixed and depends on other parameters of the scanning process, such as laser power, beam speed, and physicochemical properties of the material.
Keywords: additive manufacturing; porosity; key hole defect; melting mode; melt pool.